DOMINOES OF EQUATIONS: PLAYFUL RESOURCE FOR LEARNING ALGEBRA IN A PUBLIC SCHOOL IN THE CITY OF PARAÍSO DO TOCANTINS-TO (REMUNOM, 2024)
Algebra is a mathematical content that requires an intense level of abstraction, due to numerical values ​​expressed in literal form, that is, the use of letters to express numerical values, which may not present meaning for the majority of students, a situation that can cause considerable decline in learning, leading to a misunderstanding of school mathematical content. Given the context, the research aimed to use and evaluate the domino game of 1st degree equations to assist the teaching-learning process in the classroom. The study was developed quantitatively, aiming to evaluate a game developed to help learning first-degree equations. The game was applied in the month of August, in a class, with 40 students, from the 1st year of High School, in the morning, lasting 50 minutes, in a public school located in the city of Paraíso do Tocantins, State of Tocantins. After using the game, students were invited to answer a questionnaire with the following 3 (three) closed and 2 (two) open questions. The diagnosis and analysis of the application of the domino game of 1st degree equations demonstrate that the playful approach carried out presented values ​​equal to or greater than 70% in all questions questioned, showing good acceptance and contributing to significant learning about the algebra content studied. The Dominoes game of 1st grade equations provided a situation of socialization in a relaxed and interactive environment, generating contextualized learning that was closer to the student's daily life. Therefore, the use of playful activity was an auxiliary strategy of great relevance for learning and maintaining the study of algebra and basic mathematical operations, supporting the teacher to contextualize the content and motivate students.